English at Work: Enhancing Women’s Employability and Workplace Experiences - Sapkota , Sangita (Journal of NELTA, 2025)
In the context of the prevalent gender disparity in Nepal, the empowerment of employed women remains crucial, as only a limited number of women hold senior roles. Despite the influential impact of English on global employability and career advancement, its role in shaping women’s workplace experiences in Nepal has remained underexplored. This study explored how employed women describe their navigation of the workplace experience and how English proficiency influences their professional advancement. As narrative research, I conducted two rounds of informal interviews with four purposively sampled senior-level women from diverse fi elds. I then analyzed their responses, categorizing them into relevant themes and sub-themes, and examined them through Sen’s Capability Approach. The findings indicate that while women appreciate their roles, they face certain Barriers to excelling/ excellence, such as workplace biases and societal expectations. Additionally, English proficiency as a capability of employed women serves as a catalyst for their professionalism, both enabling opportunities and presenting obstacles, with limited proficiency resulting in inequalities. The study recommends the need for equitable workplace practices, assessing workplace dynamics, and acknowledging the role of English language proficiency for women’s well-being, thereby fostering inclusivity and gender equity in professional settings.